Effect of the fungicides tridemorph and vinclozolin on soil microorganisms and nitrogen metabolism - Banerjee, A; Banerjee, A K (Folia microbiologica, 1991)
The effects of tridemorph and vinclozolin were studied on different types of microorganisms, urea hydrolysis and nitrification in soil and in culture. The fungicides adversely affected the population of bacteria, fungi and actinomycetes as a function of time of incubation. Urea hydrolysis both in culture and soil were also inhibited by the fungicides, and tridemorph was more detrimental. In soil, 45 micrograms/g of tridemorph inhibited 50% of ammonification of urea, ID50 for nitrite production was 750 micrograms/g. In urea-hydrolyzing cultures, 80, 75 and 77 mg/L of tridemorph were the ID50 values for urea hydrolysis by Micrococcus sp., Proteus sp. and P. vulgaris respectively.
Keywords: Morpholines; morfoliny; Ammonia; Nitrates; oxazoly; močovina; Nitrogen; houby; Oxazoles; půdní mikrobiologie; Fungi; Actinomycetales; Bacteria; Soil Microbiology; Fungicides, Industrial; dusičnany; průmyslové fungicidy; amoniak; Urea; dusík